2020
DOI: 10.3389/fmicb.2020.01919
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Potential of Antimicrobial Combinations Against Methicillin-Resistant Staphylococcus aureus

Abstract: The chemotherapeutic options for methicillin-resistant Staphylococcus aureus (MRSA) infections are limited. Due to the multiple resistant MRSA, therapeutic failure has occurred frequently, even using antibiotics belonging to different categories in clinical scenarios, very recently. This study aimed to investigate the interactions between 11 antibiotics representing different mechanisms of action against MRSA strains and provide therapeutic strategies for clinical infections. Susceptibilities for MRSA strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…However, in our study, these three peptide antibiotics combined with rifampicin had 100% additive effects. We proposed that rifampicin inhibited the β subunit of bacterial RNA polymerase, while these three peptide antibiotics disrupted the bacterial cell wall synthesis, these combinations may disturb cell reproduction in different steps to enhance the antibacterial effects ( Douthit et al, 2020 ; Yu et al, 2020 ). Therefore, rifampicin could become an ideal choice for combination therapy with peptide antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, these three peptide antibiotics combined with rifampicin had 100% additive effects. We proposed that rifampicin inhibited the β subunit of bacterial RNA polymerase, while these three peptide antibiotics disrupted the bacterial cell wall synthesis, these combinations may disturb cell reproduction in different steps to enhance the antibacterial effects ( Douthit et al, 2020 ; Yu et al, 2020 ). Therefore, rifampicin could become an ideal choice for combination therapy with peptide antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, quercetin can scavenge free radicals to prevent lipid peroxidation, inhibiting tumor proliferation ( Reyes-Farias and Carrasco-Pozo, 2019 ). Also, it has been reported that the combination of quercetin with other antibiotics such as vancomycin and tetracycline possess synergistic antibacterial activity against E. coli and Staphylococcus aureus ( Qu et al, 2019 ; Yu et al, 2020 ). In addition, quercetin possesses low cytotoxicity and can increase intracellular oxidative stress in tumor cells usually at concentrations >40 mM( Vargas and Burd, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The checkerboard assay was conducted to explore the synergy effect between colistin and quercetin via determining the fractional inhibitory concentration (FIC) index ( Yu et al, 2020 ). Briefly, colistin was continuously dilute 2-fold along the x -axis, while quercetin was continuously diluted 2-fold along the y -axis to establish a matrix in 96-well plates, where each well contained different concentrations of two drugs.…”
Section: Methodsmentioning
confidence: 99%
“…The kinetics of the bactericidal action of qy17 and qy20 on S. haemolyticus were studied with an improved method ( Yu et al, 2020 ). A 96-well plate contained a bacterial suspension (5 × 10 7 CFUs/mL, final concentration) and MHB containing qy17 and qy20 (8, 16, and 32 μg/mL, final concentrations).…”
Section: Methodsmentioning
confidence: 99%